PENGARUH PENGELOLAAN KELAS TERHADAP KEEFEKTIFAN BELAJAR PESERTA DIDIK - Lukman Hakim; Fauzan Adrasyanto; Miftahir Rizqa (LPPM Universitas Cipta Mandiri, 2024)
Classroom management is an activity that needs to be planned and implemented by a teacher during the teaching and learning process. Teachers must be able to control the classroom situation and give special attention to students in order to achieve success in the learning process. The aim of this research is to expand knowledge and understanding for teaching staff so that they can increase creativity and innovation in managing classes so that they can create effective learning. The method the author uses is a literature review with a descriptive approach used in this research, where the data is analyzed through the literature review stage. The research results show the importance of the role of an educator in managing the classroom to increase students' learning effectiveness. As a teacher, first understand the material that will be taught to students so that when students ask questions, the teacher can easily give them a detailed explanation. Apart from that, teachers can also apply various learning models that can stimulate their students' thinking patterns in a positive direction. Therefore, the higher the level of creativity of an educator in managing the class, the greater the effectiveness of students in the learning process.